THE EFFECT OF JOB ROTATION ON EMPLOYEE PERFORMANCE THROUGH COMPETENCY VARIABLES IN THE EMPLOYEE SECRETARIAT SIAK REGENCY - Syofian; Seswandi, Agus; Aznuriyandi (Ekomania, 2024)
The purpose of this study was to analyze the effect of job rotation on employee performance Through competency variables on employees of the Siak Regency Regional Secretariat. The population in this study were employees involved in financial management in all Regional Government Work Units (SKPD) of Bengkalis Regency. The sample in the study was The population in this study were all employees of the Siak Regency Regional Secretariat totaling 140 people with the exception of 6 people consisting. so the number of samples was 134 people. The sampling technique used in this study was non-probability sampling. Data collection techniques using questionnaires and distribution using google forms. The data analysis technique in this study was Structural Equation Modeling (SEM) using SmartPLS 3.0 as a data processing tool. The results of this study indicate that job rotation has a positive and significant effect on employee competence at the Siak Regency Regional Secretariat. Employee competence has a positive and significant effect on performance. When employees who have high competence are able to complete tasks more effectively, efficiently, and innovatively and employee performance will also increase. Job rotation has a positive and significant effect on employee performance. Competence significantly mediates the effect of job rotation on performance.